2022
DOI: 10.1371/journal.pone.0272597
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work-life and turnover intentions among the Ghanaian nursing workforce: A multicentre study

Abstract: Introduction Attrition of the Nursing Workforce from low-and middle-income countries to high-resourced settings is a reality that has escalated in the current Coronavirus pandemic due to varied reasons. With increased job stress resulting from the pandemic, the Quality of Work-Life of the Nursing Workforce is affected, with its effect on poor quality care to the client. This study sought to assess the perception of the Nursing Workforce about the Quality of Work-Life, and the factors that predict turnover inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Employing Easton and Van Laar's measure, McFadden et al (2020) found half of a sample of 3290 United Kingdom (UK) health and social care workers experienced high QoWL and just over one-third (34.6%) experienced low QoWL. Variations in the measurement notwithstanding, there is evidence that QoWL is associated with turnover intention in many studies, including primary and tertiary care nurses (Kaddourah et al, 2018;Poku et al, 2022) and hospital employees (Shukla et al, 2017). There are few studies that measure QoWL directly in occupational therapists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employing Easton and Van Laar's measure, McFadden et al (2020) found half of a sample of 3290 United Kingdom (UK) health and social care workers experienced high QoWL and just over one-third (34.6%) experienced low QoWL. Variations in the measurement notwithstanding, there is evidence that QoWL is associated with turnover intention in many studies, including primary and tertiary care nurses (Kaddourah et al, 2018;Poku et al, 2022) and hospital employees (Shukla et al, 2017). There are few studies that measure QoWL directly in occupational therapists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, promoting employee well-being leads to decrease employee turnover [10]. Providing psychological and social support through counselling promotes the quality of work-life [11]. With time, newly considered factors such as leader member exchange, workplace culture, happiness, joy in the workplace, career management, innovative work behaviour and employee delight are equally important and have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the QWL directly influences an organisation's ability to delight its stakeholders and efforts geared towards improving the QWL foster efficient and effective distribution of resources that will boost employee productivity and workforce stability (Ishfaq et al ., 2022). Another thing that makes management of the QWL problematic for organisations lies in the hours of work, workload and work pressure experienced by the workforce (Poku et al , 2022). These are elements of being a workaholic in the workplace.…”
Section: Introductionmentioning
confidence: 99%